2010
DOI: 10.1063/1.3319672
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular dynamics in crowded environments

Abstract: The structural and dynamical properties of macromolecules in confining or crowded environments are different from those in simple bulk liquids. In this paper, both the conformational and diffusional dynamics of globular polymers are studied in solutions containing fixed spherical obstacles. These properties are studied as a function of obstacle volume fraction and size, as well as polymer chain length. The results are obtained using a hybrid scheme that combines multiparticle collision dynamics of the solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 56 publications
(76 reference statements)
0
25
0
Order By: Relevance
“…Multiparticle collision dynamics, also known as stochastic rotation dynamics [13], is a particle-based technique for complex fluids that includes thermal fluctuations and hydrodynamic interactions [10]. Multiparticle collision dynamics has proven to be capable of simulating many soft-matter systems, including colloid dynamics [11,14,15], polymer and proteins dynamics [16][17][18][19][20][21], vesicles [22] and reactive systems [23,24]. Multiparticle collision dynamics has also been employed to investigate the properties of chemical reaction in crowded environments; i.e., media containing obstacles [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Multiparticle collision dynamics, also known as stochastic rotation dynamics [13], is a particle-based technique for complex fluids that includes thermal fluctuations and hydrodynamic interactions [10]. Multiparticle collision dynamics has proven to be capable of simulating many soft-matter systems, including colloid dynamics [11,14,15], polymer and proteins dynamics [16][17][18][19][20][21], vesicles [22] and reactive systems [23,24]. Multiparticle collision dynamics has also been employed to investigate the properties of chemical reaction in crowded environments; i.e., media containing obstacles [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…[8] Polymer diffusion [9] and dynamics [10] under confinement, conformation and molecular mobility of polymers confined in nanochannels [11] (e.g., in urea), and so on have also been studied.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Studies have been reported on crystallization in ultra thin polymer films [7] and in small nanodomains.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrodynamic interactions are therefore key to understanding both the motion of proteins in dilute and in crowding conditions. This has been pointed out in seminal theoretical and experimental work [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%